Cytotoxic effects of Argentinean plant extracts on tumour and normal cell lines - Mamone, L.; Di venosa, G.; Valla, J. J.; Rodriguez, L.; Gándara, L.; Batlle, A.; Heinrich, M.; Juarranz, A.; Sanz- rodriguez, F.; Casas, A. (Cellular and Molecular Biology, 2011)
In the search for possible new anti-cancer agents, we investigated the effects of 75 aqueous and methanol extracts from 41 Argentinean plant species. The effect in cell growth was evaluated in the LM2 mammary adenocarcinoma cells. In a second stage, the highly active selected extracts were assayed in 3 other tumour cell lines: melanoma B16, bladder MB49 and lung A549; and 3 normal cell lines: mammary Hb4a and keratinocytes PAM212 and HaCat. Eight methanol extracts were found to be highly cytotoxic: Collaea argentina leaf, Iochroma australe leaf, Ipomoea bonariensis flower, Jacaranda mimosifolia flower, Solanum amygdalifolium flower, Solanum chacoense leaf, Solanum sisymbriifolium flower and Solanum verbascifolium flower. However, extract inhibition on cell growth was highly dependent on cell type. In general, except for the highly resistant cell lines, the inhibitory concentrations 50% were in the range of 10-150 µg/ml The eight extracts highly inhibited cell growth in a concentration-dependent manner, and in general the methanol extracts were always more active than the aqueous. Murine cells appear to be more sensitive than human cells to the cytotoxic action of the plant extracts. The human melanoma B16 line was the most resistant to four of the extracts. In terms of selectivity, S. verbascifolium was the species which showed most selectivity for tumour cells. Overall, this is one of the first studies focusing on southern South American native plants and their biological effects. Since some species of 5 genera analyzed have been reported to possess different degrees of alkaloid content, we examined microtubule structures after extract treatments. The eight extracts induced destabilization, condensation and aggregation of microtubules in LM2 cells, although no depolarization, typical of Vinca alkaloids damage was observed. In a near future, antitumour activity of purified fractions of the extracts administered at non-toxic doses will be assayed in transplantable murine tumour models.